The effect of human chorionic gonadotropin on the In vitro development of immature to mature human oocytes: A randomized controlled study - Chananya Tantitham; Sitanan Panunumpa; Chonthicha Satirapod (Wolters Kluwer Medknow Publications, 2020)
Context: In controlled ovarian hyperstimulation cycles, 15% of oocytes have been proven to be immature. Key factors include failure in signal transmission from the cumulus cell to the oocyte, insufficient level of luteinizing hormone, and internal conditions of the oocyte itself. Aims: The aim of the present study was to investigate the effect of human chorionic gonadotropin (hCG) on the in vitro maturity of partially cumulus-denuded immature oocytes collected after controlled ovarian stimulation for in vitro fertilization (IVF). Settings and Design: This was a prospective, randomized controlled design at the department of obstetrics and gynaecology, university hospital. Subjects and Methods: Infertile women underwent gonadotropin-releasing hormone antagonist stimulated protocol for IVF with final maturation triggered by hCG, partially cumulus-denuded immature human oocytes were allocated to two groups: the first was treated with fertilization medium and the second was treated with fertilization medium and hCG. They were cultured for 24 h. Outcomes measured were the oocyte maturation rates to metaphase II (MII) and glucose-6-phosphate dehydrogenase (G6PD) activity of in vitro maturation (IVM) mature oocytes which represent the oocyte quality. Statistical Analysis Used: The Mann-Whitney U-test and One-way ANOVA were used to compare continuous variables, and Chi-square was used for categorical data. Results: In all, 250 immature stimulated oocytes were allocated (125 per group). The maturation rate was higher in the hCG supplement group (48% vs. 39.2%) without significance. The positive brilliant cresyl blue results among the MII oocytes developed from the metaphase I (MI) were significantly higher in the hCG group (P = 0.001). Conclusions: Rescue IVM in fertilization culture medium plus hCG was slightly better than that in the only fertilization culture. MII oocytes developed from MI in hCG supplemented medium had a higher quality based on the measured G6PD activity.